Social and economics repercussions of the table olive sector - M. David García Brenes (Grasas y Aceites, 2007)
This work studies the most relevant economic and social elements concerning the table olive in Andalusia, from the grove to the processing and seasoning industry. The importance of worldwide agrarian production is analysed along with its social implications and recent technological developments. The fact that the table olive industry generates more wealth and employment in relative terms than the olive oil industry is also emphasized.